2008
DOI: 10.1073/pnas.0802390105
|View full text |Cite
|
Sign up to set email alerts
|

Synapse formation and clustering of neuroligin-2 in the absence of GABA A receptors

Abstract: GABAergic synapses are crucial for brain function, but the mechanisms underlying inhibitory synaptogenesis are unclear. Here, we show that postnatal Purkinje cells (PCs) of GABAA␣1 knockout (KO) mice express transiently the ␣3 subunit, leading to the assembly of functional GABAA receptors and initial normal formation of inhibitory synapses, that are retained until adulthood. Subsequently, down-regulation of the ␣3 subunit causes a complete loss of GABAergic postsynaptic currents, resulting in a decreased rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
114
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(133 citation statements)
references
References 49 publications
16
114
1
Order By: Relevance
“…The specificity of MGL antibodies has been verified by blank labeling in global MGL-KO brains in our previous studies (22,35). By double immunofluorescence for MGL and carbonic anhydrase 8 (Car8), a marker of PCs (38), punctate MGL labeling was prominent in the neuropil of the molecular layer (ML), but was absent in Car8-labeled PC dendrites and somata (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The specificity of MGL antibodies has been verified by blank labeling in global MGL-KO brains in our previous studies (22,35). By double immunofluorescence for MGL and carbonic anhydrase 8 (Car8), a marker of PCs (38), punctate MGL labeling was prominent in the neuropil of the molecular layer (ML), but was absent in Car8-labeled PC dendrites and somata (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…5) In contrast, the DGC is not altered in neurons lacking functional GABAergic transmission or gephyrin clusters (Fig. 4D, G) [105,74], indicating that its formation and postsynaptic localization is not dependent on GABA A R or gephyrin. 6) Preservation of NL2 clustering in the absence of GABA A R and/or gephyrin suggests a mandatory association between NL2 and S-SCAM/β-dystroglycan complex (Fig.…”
Section: Model Of Psd Protein Clustering At Gabaergic Synapsesmentioning
confidence: 94%
“…4) Gephyrin clustering, but not NL2 clustering, requires the presence of postsynaptic GABA A R (Fig. 4C-D) [105], in particular those containing the α2 subunit (Fig. 4G) [74].…”
Section: Model Of Psd Protein Clustering At Gabaergic Synapsesmentioning
confidence: 96%
“…In the brainstem, where GABA and glycine are often coreleased, lack of NL2 leads to deficits in both GABAergic and glycinergic neurotransmission (G. Aramuni and W. Zhang, personal communication). Furthermore, NL2 clusters are detected at very early stages of inhibitory postsynapse differentiation (Varoqueaux et al, 2004;Patrizi et al, 2008), and in vitro studies have suggested that NL2 may contribute to the recruitment of GABA A receptors (Dong et al, 2007). Thus, there is emerging evidence for a central role of NL2 in organizing inhibitory synapse assembly and function.…”
Section: Introductionmentioning
confidence: 99%